CHARACTERISTICS OF HYDRODYNAMICS AND FLUSHING TIME IN NAI LAGOON (NINH THUAN) - RESULTS BASED ON THE DELFT3D - Vinh, Vu Duy; Quan, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2015)
This paper presents the results of research and estimate on the hydrodynamic characteristics and flushing time in Nai lagoon (Ninh Thuan province). The 3D model was set up based on Delft3D modelling system and calibration, validation through measured data of currents, water elevation in typical seasons (rainy and dry). The results showed that tidal amplitude in the lagoon decreases 0.05 - 0.2 m compared to the value in the open sea. The tidal lag in the lagoon is about 1 hour (high tide) and about 1 - 3 hours for low tide. Current velocity in Nai lagoon is always less than 0.2 m/s. Flushing time in Nai lagoon is fairly good compared with other lagoons in Vietnam as well as in the world with the value of about 2.4 - 2.7 days.